Canine visceral leishmaniasis in the Northeast Region of Brazil. Issue 1 (December 2016) - Brito, Flávio; Langoni, Helio; Silva, Rodrigo; Rotondano, Tereza; Melo, Marcia; Paz, Giselle
Abstract Background Visceral leishmaniasis (VL) is a zoonosis that affects dogs and other mammals, including humans. Contact with dogs is a major risk factor for humans. This disease is endemic in several regions of Brazil. The aim of this study was to determine the prevalence ofLeishmania spp. infection in dogs and to correlate it with possible risk factors. Methods Blood samples were collected from 391 dogs of different ages, breeds, and both genders, coming from Campina Grande, Paraíba state, Brazil. An epidemiological questionnaire was employed in order to identify risk factors associated with the disease. Serological tests were performed using indirect immunofluorescence, enzyme-linked immunosorbent assay (ELISA S7®) and polymerase chain reaction. Results Leishmania spp. antibodies were detected in 33 (8.4 %) and 17 (4.3 %) dogs according to the indirect immunofluorescence test (IFAT) and enzyme-linked immunosorbent assay (ELISA S7®), respectively. PCR results indicated the presence ofL. chagasi DNA in only eight (2 %) blood samples. There was a significant association between reactive animals and contact with animals from different houses (OR = 4.1;p = 0.02). Conclusions It is suggested that CVL may occur in urban areas. Moreover, it is demonstrated that the association among different diagnostic tests may lead to a more accurate identification of positive animals, which might help to improve the disease control and prevent euthanasia in false-positive results.